Pemberdayaan Masyarakat Kelompok Usaha Budidaya Itik Petelur dengan Pemberian Pakan Prebiotik di Desa Pallangga Kabupaten Gowa - Tang, Beddu; Samsualam, Samsualam; Anwar, Anwar; Syaggaf, Andi Waliana; Danial, Danial (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2025)
Community empowerment is related to efforts to overcome development problems such as unemployment, poverty, and inequality. Pallangga Village allows for community-based development (empowerment) because it has extensive natural resources in the field of animal husbandry. Increasing income through laying duck cultivation needs to continue even though the results are still inadequate and do not meet expectations. This activity aims to provide knowledge and skills for partners in an effort to increase income through laying duck cultivation. The target of this activity is the BUMDES group in Pallangga Village. This activity was held on July 11 2024 and August 29 2024 at the Pallangga village meeting hall. The training method implemented consisted of delivering material, discussions and questions and answers, as well as demonstrations on making prebiotic feed for cultivating laying ducks. The results of the activity showed that the people (BUMDES) of Pallangga Village were very enthusiastic about taking part in the training activities, seen from the number of participants attending and active, from previously less enthusiastic residents to more enthusiastic and enthusiastic participants, numbering 25 people. The results of this activity can increase the production of laying ducks as measured by the number of ducks that lay eggs every day and an increase in the number of ducks that lay eggs.